Kıraat Sorunu - Halis Albayrak (Dini Araştırmalar, 2015)
Kıraat problem has existed as a coplex and difficult one among muslim scholars from the very beginning. Different ways of reading the Quran (kıraat) existed even while the prophet was alive. Same scholars considered that all sahih kıraat had come from the Prophet Muhammed. In other words they were directly originated from revelation (wahy). It seems that the reasons of kıraat are to a large extent historical and social. Particularly the undevelopped Arabic script which allowed to different ways of readings might be considered one of the important reasons for kıraat. The Works of collecting kıraat had lasted during the three centuries after hicra and to a great extent were copleted in the forth century .Ebu Bekr Ibn Mucahid reduced the number of kıraat to seven in his well known work ei-Kıraatu 's-Seb “